Respuesta :
-3x + 2y = -3
4x - y = -1
2(4x - y = -1)
-3x +2y = -3
8x -2y = -2
-5x = -5
/-5
X = 1
4x - y = -1
2(4x - y = -1)
-3x +2y = -3
8x -2y = -2
-5x = -5
/-5
X = 1
Answer:
x = -1, y = -3
Step-by-step explanation:
Let's start by solving -3x + 2y = -3 for x.
-3x + 2y = -3
Subtract 2y from both sides of the equation.
-3x = -2y - 3
Divide both sides by -3.
x = -1/3(-2y - 3)
Multiply -1/3 by -2y - 3.
x = 2/3y + 1
Substitute 2/3y + 1 for x in 4x - y = -1
4(2/3y + 1) - y = -1
Multiply 4 by 2/3y + 1.
8/3y + 4 - y = -1
Add 8/3y to -y.
5/3y + 4 = -1
Subtract 4 from both sides of the equation.
5/3y = -5
Multiply both sides by 3/5.
y = -3
Substitute -3 for y in x = 2/3y + 1. Because the resulting equation contains only one variable, you can solve for x directly.
x = 2/3(-3) + 1
Multiply 2/3 by -3.
x = -2 + 1
Add 1 to -2.
x = -1
The system is now solved. x = -1, and y = -3.
Work check:
-3(-1) + 2(-3) = -3
3 + (-6) = -3 is true.
4(-1) - (-3) = -1
-4 - (-3) = -1
-4 + 3 = -1 is true.